Effect of Functionalized Groups on Gas‐Adsorption Properties: Syntheses of Functionalized Microporous Metal–Organic Frameworks and Their High Gas‐Storage Capacity. Issue 5 (20th December 2013) - Wang, Yanlong; Tan, Chunhong; Sun, Zhihao; Xue, Zhenzhen; Zhu, Qilong; Shen, Chaojun; Wen, Yuehong; Hu, Shengmin; Wang, Yong; Sheng, Tianlu; Wu, Xintao
Abstract The microporous metal–organic framework (MMOF) Zn4O(L1)2⋅9 DMF⋅9 H2O (1‐H) and its functionalized derivatives Zn4O(L1‐CH3)2⋅9 DMF⋅9 H2O (2‐CH3) and Zn4O(L1‐Cl)2⋅9 DMF⋅9 H2O (3‐Cl) have been synthesized and characterized (H3L1=4‐[N, N‐bis(4‐methylbenzoic acid)amino]benzoic acid, H3L1‐CH3=4‐[N, N‐bis(4‐methylbenzoic acid)amino]‐2‐methylbenzoic acid, H3L1‐Cl=4‐[N, N‐bis(4‐methylbenzoic acid)amino]‐2‐chlorobenzoic acid). Single‐crystal X‐ray diffraction analyses confirmed that the two functionalized MMOFs are isostructural to their parent MMOF, and are twofold interpenetrated three‐dimensional (3D) microporous frameworks. All of the samples possess enduring porosity with Langmuir surface areas over 1950 cm2 g−1. Their pore volumes and surface areas decrease in the order 1‐H>2‐CH3>3‐Cl. Gas‐adsorption studies show that the H2 uptakes of these samples are among the highest of the MMOFs (2.37 wt % for 3‐Cl at 77 K and 1 bar), although their structures are interpenetrating. Furthermore, this work reveals that the adsorbate–adsorbent interaction plays a more important role in the gas‐adsorption properties of these samples at low pressure, whereas the effects of the pore volumes and surface areas dominate the gas‐adsorption properties at high pressure.